The impact of private equity on firms' innovation activity - Kevin Amess; Joel Stiebale; Mike Wright (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
The paper analyses the impact of private equity (PE) backed leveraged buyouts (LBOs) on innovation output (patenting). Using a sample of 407 UK deals we find that LBOs have a positive causal effect on patent stock and quality-adjusted patent stock. Our results imply a 6% increase in quality-adjusted patent stock three years after the deal. The increase in innovation activity is concentrated among private-to-private transactions with a 14% increase in the quality-adjusted patent stock. Further analysis supports the argument that PE firms facilitate the relaxation of financial constraints. We also rule out alternative explanations for portfolio firms' higher patenting activity. Our findings suggest that PE firms do not promote short-term cost-cutting at the expense of entrepreneurial investment opportunities with a long-term payoff.
Keywords: D22; G32; G34; L26; 330; private equity; leveraged buyout; entrepreneurial buyouts; innovation